La cerámica de los afluentes del Guaporé en la colección de Erland von Nordenskiöld - Betancourt, Carla Jaimes (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
During his journey along the Guaporé and its tributaries between 1908 and 1909, Erland von Norden skiöld collected ceramic sherds from various sites in the region. These finds, now located in the Världskulturmuseet in Gothenburg, Sweden, have remained unpublished until now. Since archaeological data on the Guaporé region are still scarce, I present a detailed analysis of the entire collection. The materials derive from sites enclosed by circular ditches that may date to the same late pre-Hispanic period. It is, therefore, striking to see that each of the sites visited by Norden skiöld yielded ceramics with distinct regional styles. It is not possible to determine if this heterogeneity refl ects cultural diversity in the region prior to the Spanish contact or chronological differences without further archaeological investigation. The article will be available as a PDF in the near future.